Firefighters occupational exposure assessment: a systematic literature review - Teixeira, Tatiana (2021)
Over the years, the evolution of forest fires has occurred as a result of the evolution of the human species. However, forest fires are still a major challenge for society, placing firefighters with greater occupational exposure. The present study has as main objective to carry out a systematic review of the literature on the main techniques and variables for assessing the occupational exposure of firefighters, during the fight against forest fires. The systematic review utilised The Preferred Reporting Items for Systematic Reviews and Meta-Analyses: The PRISMA Statementmethodology. This methodology was applied in the Scopus, Web of Science, Pubmed and Academic Search Complete databases with different keywords. The review will include articles written in English only. In the present study, 34 articles were included, in which it was found that exposure to smoking is the most studied variable, and it was in 2019 that a greater evolution of studies in this area of research was observed. Regarding the variables, the studies were organised in groups. Here it is possible to check the different variables selected by the authors and the methods and equipment applied.Discussion: The fact that firefighters carry out their tasks in diverse scenarios and extreme conditions has hindered the application of innovative equipment. It is necessary to combine different variables and equipment for the assessment of occupational exposure. However, it is not always possible to develop this type of equipment in order to be inserted from the user's perspective, from the perspective of the environment, where it will be applied, and from an economic perspective, making it difficult to effectively apply it in the field. As future perspectives, it is recommended that new variables are introduced together, in order to improve the assessment of occupational exposure, namely, through the use of carbon monoxide (CO) and lactate assessment.